HUBUNGAN BEBAN KERJA PERAWAT DENGAN PENERAPAN PRINSIP TUJUH BENAR DALAM PEMBERIAN OBAT PADA PASIEN DI RUANG RAWAT INAP - Ahsan, Ahsan; Noviyanti, Linda Wieke; Primanoviasari, Titis Sukma (Jurnal Kesehatan Mesencephalon, 2018)
Perception that the administration of seven drugs correctly making burden workload, so that nurses do nursing care activities in a hurry. Treatment errors are not only caused by nurses but also because patient themselves do not follow existing procedures. The purpose of this study was to identify the relationship between nurses workload and the application of the seven principles of correctness in drug delivery to patients in the inpatient ward. This research is a correlational research with cross sectional design approach. The study was conducted on 26 March - 6 April 2018 in patient room B, C, D and E Wava Husada Kepanjen Hospital. The population of this study was the nurses, 46 nurses with proportional random sampling. Data collection were using questionnaires about nurses workload and observation sheets about the application of the seven principles of drug administration. Data analysis was used Spearman Rank test and data presentation in the form of frequency distribution and narrative tables. The result Spearman Rank test it was found that there was a significant relationship between the workload of nurses and the application of the principle 7 correct drug administration. The workload of nurses should be properly regulated so as not to interfere with the application of the seven principles correctly in the administration of drugs to patientsKeywords: Nurse Workload, Principle Seven True Drug Giving